The simplified expression that represents the area of the parallelogram is 2x^3 - 6x^2 -14x + 24
Area of a parallelogram = base * height
Given the following
Base = 2x^2 + 2x - 6
Height = x - 4
Substitute into the formula to have:
Area of a parallelogram= (x-4)(2x^2 + 2x - 6)
Area of a parallelogram= 2x^3 + 2x^2 - 6x - 8x^2 - 8x + 24
Area of a parallelogram= 2x^3 - 6x^2 -14x + 24
Hence the simplified expression that represents the area of the parallelogram is 2x^3 - 6x^2 -14x + 24
Learn more on area of parallelogram here: https://brainly.com/question/8032559